REMA topography and AntarcticaLC2000 for WRF - Gerber, Franziska; Lehning, Michael (2021)
Reference Elevation Model of Antarctica (REMA) topography and AntarcticaLC2000 landuse dataare now available as static data input for the Weather Research and Forecasting model (WRF). Topographyand landuse are made available at a spatial resolution of 1 km. This documentation describes the methodsapplied to convert REMA and AntarcticaLC2000 to WRF readable format and shows how this improvesthe representation of the Antarctic topography and landuse categories over coastal Antarctic regions.